2013
DOI: 10.5692/clinicalneurol.53.827
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae meningitis treated successfully with polymyxin B-immobilized fiber therapy: a case report

Abstract: A-61-year old man was admitted to our hospital with fever and severe disturbance of consciousness. He was diagnosed with Streptococcus pneumoniae meningitis on the basis of cerebrospinal fluid (CSF) analysis and urinary antigen detection by immunochromatography. Although he was treated with dexamethasone and antibiotics, his general status worsened as systemic inflammatory response syndrome (SIRS), disseminated intravascular coagulation (DIC), and status epileptics developed. Following treatment with polymyxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Clinical experience with PMX‐DHP for meningitis is limited though and has not been described in English‐language publications. Indeed, our first such case (case 1 in the present study) was reported in Japanese in 2013 …”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Clinical experience with PMX‐DHP for meningitis is limited though and has not been described in English‐language publications. Indeed, our first such case (case 1 in the present study) was reported in Japanese in 2013 …”
Section: Introductionsupporting
confidence: 53%
“…A 61‐year‐old man presented with impaired consciousness with a GCS score of 5 (E1V1M3), SIRS (temperature, 39.6°C; leukocytes, 5800 cells/μL; pulse rate, 110/min; respiratory rate, 48/min), and elevated C‐reactive protein (8.12 mg/dL) . CSF pressure was elevated at ≥625 mmH 2 O; analysis revealed pleocytosis with 480 cells/μL (78% multinuclear cells) and elevated protein at 536 mg/dL with low glucose (CSF:blood glucose ratio 0.011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation